Investigating cochlear cellular dynamics in neurofibromatosis type 2-associated schwannomatosis: a histopathological study - Reef K. Al-Asad; Reef K. Al-Asad; Drew J. Montigny; Drew J. Montigny; Jennifer T. O’Malley; D. Bradley Welling; David H. Jung; David H. Jung; Andreas H. Eckhard; Judith S. Kempfle; Judith S. Kempfle; Judith S. Kempfle; et al. (Frontiers in Neurology)
Sensorineural hearing loss (SNHL) is a hallmark symptom in patients with neurofibromatosis type 2-associated schwannomatosis (NF2-SWN), a genetic condition caused by mutations in the Neurofibromin II gene that encodes the tumor suppressor protein Moesin-Ezrin-Radixin-Like Protein (Merlin; also known as schwannomin). These mutations lead to the development of various tumors, including schwannomas, ependymomas and meningiomas along the vestibular nerve and the cerebellopontine angle. Original theories attributed SNHL in NF2-SWN to the mechanical compression of the vestibulocochlear nerve from the tumor itself, in addition to secretion of toxic tumor byproducts. However, the observation that SNHL can progress independently of tumor size and growth dynamics challenges this view and reveals a critical gap in our understanding of its underlying etiology. To better define cochlear changes associated with hearing loss in NF2-SWN, immunohistochemical cell type markers were used on archival postmortem temporal bone samples from both NF2-SWN patients and healthy controls and quantified the number and cellular density of neural (TUJ1), glial (SOX10), and immune cells (IBA1) within apical, middle, and basal turns of the cochlea. Our findings demonstrated a significant loss of spiral ganglion neurons, a slight increase of Schwann cells, and marked activation of cochlear macrophages in NF2-SWN cases. These findings indicate the contribution of cochlear macrophage-mediated inflammation and Schwann cell dysregulation in the pathophysiology of SNHL in NF2-SWN.